Peran Kode Etik Notaris Dalam Membangun Integritas Notaris Di Era 4.0 - Betty Ivana Prasetyawati; Paramita Prananingtyas (Magister Kenotariatan Universitas Diponegoro, 2022)
A Notary is a public official that has the authority to create authentic deeds and other powers as referred in Act No. 2 of 2014. In the world of notaries, the notary standards of ethics have been described in the notary code of ethics determined by the Indonesian Notary Association and must be obeyed by all notaries concerned. These codes of conduct should be the self-regulation of the profession and its implementation. The start of the industrial revolution 4.0 brought many changes to the world. Ministry of industry on a large and comprehensive scale to create a business that processes simpler, faster, easier, and cheaper to Making Indonesia 4.0 become a reality. Notaries are expected to actively participate in the licensing service process that is integrated electronically, or can be called as Online Single Submission (OSS). The urgency of reforming the code of ethics for the professional posititon of a notary as the practice of Indonesian notary in the industrial revolution 4.0 era, for the sake of creating notaries who have high integrity and morality to carry out their duties.Keywords : Notary; Code of Ethics; 4.0 Era AbstrakNotaris merupakan pejabat umum yang berwenang untuk membuat akta otentik dan kewenangan lainnya, sebagaimana dimaksud dalam Undang-Undang Nomor 2 Tahun 2014.Di dalam dunia kenotariatan standar etik Notaris telah dijabarkan dalam Kode Etik Notaris yang ditentukan oleh Ikatan Notaris Indonesia (INI) dan wajib dipatuhi oleh segenap Notaris.Kode Etik harus menjadi self-regulation dari profesi dan pelaksanaannya. Dimulainya revolusi industry 4.0 membawa banyak perubahan bagi dunia, Kementrian Perindustrian secara besar-besaran dan menyeluruh membuat business process menjadi lebih sederhana, cepat, mudah dan murah demi mewujudkan Making Indonesia 4. Para notaris diharapkan berpartisipasi aktif dalam proses pelayanan perizinan yang terintegrasi secara elektronik, atau online single submission (OSS). Urgensi pembaharuan kode etik jabatan notaris bagi praktik kenotariatan Indonesia di era 4.0 demi terciptanya notaris yang memiliki integritas dan moralitas yang tinggi dalam menjalankan tugas jabatannya.Kata Kunci : Notaris; Kode Etik; Era 4.0